2019
DOI: 10.1002/er.4772
|View full text |Cite
|
Sign up to set email alerts
|

Climate applicability study of building envelopes containing phase change materials

Abstract: Summary Building envelopes incorporating phase change materials (PCMs) can contribute to reducing the energy consumption of buildings and enhance indoor thermal environment comfort. In this study, two building models were developed in EnergyPlus to explore the applicability of using PCMs in different climate zones. Six significantly different cities from five climate zones in China have been investigated. The simulation results reflected that for climates with small fluctuation weather conditions, PCMs with ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…They concluded that a PCM with a melting point of 1°C to 3°C above the average building temperature is able to attain its optimal diurnal heat storage. It has been formerly stated that the efficiency of PCM in building applications is directly influenced by climatic conditions . Souayfane et al showed a strong relation between the climate condition and the effective performance of PCM.…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that a PCM with a melting point of 1°C to 3°C above the average building temperature is able to attain its optimal diurnal heat storage. It has been formerly stated that the efficiency of PCM in building applications is directly influenced by climatic conditions . Souayfane et al showed a strong relation between the climate condition and the effective performance of PCM.…”
Section: Methodsmentioning
confidence: 99%
“…The price of oil and fossil fuels is increasing, and this issue has turned the amount of energy consumption and its production method, into one of the main challenges in developing countries. In recent decades, the energy demand of our society, especially in the building sector, has been steadily increasing [1]. The energy consumption of buildings constitutes about 40% of the total energy consumption in developed and developing countries [2].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies investigated dynamic properties, life cycle cost implications, and performance of PCMs on buildings' interior surfaces. [23][24][25][26] Incomplete solidification was found to be a major drawback of TESs incorporating PCMs into the passive cooling of building. 27 Studies have also reported the usefulness of PCMs by employing free cooling and active cooling applications of PCMs along with their limitations in terms of size, placement, and heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous research articles have examined PCMs integrated into building envelope components to improve the space thermal comfort and energy performance. Other studies investigated dynamic properties, life cycle cost implications, and performance of PCMs on buildings' interior surfaces 23‐26 . Incomplete solidification was found to be a major drawback of TESs incorporating PCMs into the passive cooling of building 27 .…”
Section: Introductionmentioning
confidence: 99%